A Assessment of long distance chasing photometer (NAG-ADF-300-2) by estimating the drug atenolol with ammonium molybdate via continuous flow injection analysis - Elham N. Mezaal N. Mezaal (مجلة بغداد للعلوم)
Atenolol was used with ammonium molybdate to prove the efficiency, reliability and repeatability of the long distance chasing photometer (NAG-ADF-300-2) using continuous flow injection analysis. The method is based on reaction between atenolol and ammonium molybdate in an aqueous medium to obtain a dark brown precipitate. Optimum parameters was studied to increase the sensitivity for developed method. A linear range for calibration graph was 0.1-3.5 mmol/L for cell A and 0.3-3.5 mmol/L for cell B, and LOD 133.1680 ng/100 µL and 532.6720 ng/100 µL for cell A and cell B respectively with correlation coefficient (r) 0.9910 for cell A and 0.9901 for cell B, RSD% was lower than 1%, (n=8) for the determination of atenolol at concentration (0.5, 0.7 and 5) mmol/L respectively. The results were compared with classical method UV-Spectrophotometric at λ max=270 nm using the standard addition method via the use of t-test, at 95% confidence level. The comparison of data explain that long distance chasing photometer (NAG-ADF-300-2) is the choice with excellent extended detection and wide application.